Properties of nano-structured zinc oxide thin films for ultraviolet photoconductive sensor applications / Mohamad Hafiz Mamat - Mamat, Mohamad Hafiz (2009)
Nanostructured zinc oxide (ZnO) materials in thin film structure have been synthesized using the sol-gel method. The thin film depositions have been carried out by spin-coating technique and hydrothermal aqueous chemical growth method on silicon and glass substrates. The thin films were annealed for 1 hour before characterization process. The surface morphologies of prepared ZnO thin films were observed using Field Emission Scanning Electron Microscopy (FESEM) and Scanning Electron Microscopy (SEM) to investigate the evolution of ZnO particle and surface morphology. The structural properties of ZnO thin films were characterized using X-Ray Diffraction (XRD) for purity and crystallinity of ZnO thin films and particle size estimation. The optical properties of ZnO thin films were examined using UV-Vis-NIR spectrophotometer for transmittance, absorption coefficient, band gap energy, carrier concentration, porosity and Urbach energy study. The optical properties of ZnO thin films also were studied using Photoluminescence (PL) spectrophotometer to investigate the luminescence properties, crystallinity and defects state of ZnO materials. The electrical properties were investigated using current-voltage (I-V) measurement to study the conductance behavior of the thin films. ZnO thin film-based ultraviolet (UV) sensors have been prepared by sol-gel spin-coating method. The sensors have been characterized using I-V measurement system under UV lamp irradiation to investigate the response of ZnO thin films to the UV light.